A influência das atividades extracurriculares junto à proficiênciaacadêmica - Neyfsom Carlos Fernandes Matias (2011)
Extracurricular activities have positive impacts on social interactions, in connection with the academic institution, and especially in academic proficiency. In Brazil, there is the expansion of social and educational activities that most often were developed by nongovernmental organizations (NGOs), aiming to serve children and adolescents outside the formal school schedule. Collaboration with these institutions has been developed in this country with the aim of promoting the Brazilian full-time education. This fact is occur under two justifications: first that promote the social protection of the treated and the second that involvement in extracurricular activities boost school performance. This thesis aims to investigate whether the academic proficiency of students in an extracurricular program, developed by NGOs in partnership with the Municipality of Belo Horizonte, is higher compared to non-participants. The study hypothesis is that students frequent the activities of NGOs would present superior academic proficiency. Survey participants were 1133 students in the second year of schooling, registered in municipal schools, from the eastern region of Belo Horizonte. Of these, 107 were participating in the activities offered by NGO. To measure academic proficiency, was used the notes of Provinha Brasil (PB), applied in 2009, which were compared between participants and nonparticipants of NGO´s. Was observed that in eight institutions, were offered schooling activities and in other two it were sports and cultural. A school predominance has been detected in the daily implementation of activities. Based in these on our results, the increasing performance of students on exams were observed in cycle of evaluation. The results did not corroborate the hypothesis of the study and showed that students participating in the activities offered by the NGOs did not show superior results compared to the others, pointing that the activities did not influence the academic proficiency. Being a student of some schools resulted in higher grades in PB, relative to other. It was concluded that besides the students linked to NGOs not stand out compared to others, it is necessary to research more on the subject because the activities that the group of nonparticipants did out of school that may have influenced its outcome were not investigated. This fact highlights the need to understand this study as exploratory, but it contributes to initial information. Furthermore, it is also important to consider other issues in future studies, which allow the observation of the most relevant aspects, such as the intelligence, motivation, socioeconomic status, parental involvement in children's education, family environment resources and activities extracurricular. The non-inclusion of this variables is a limitation of this study.